Alopecia areata – a therapeutic problem? - Domin, Agnieszka; Domin, Piotr (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Alopecia areata is a disease affecting the whole population. The main symptoms are regions of baldness on the head, it also sometimes affects other hairbearing areas of the skin. The etiology is considered to be autoimmunologic cause. There are few clinical variants of alopecia areata. Diagnosis mainly is made on clinical features, sometimes biopsy is helpful. The process of alopecia development and hair —regrowth is unpredictable. In differential diagnosis there are considered head dermatoses and systemic diseases. The presence of alopecia areata predisposes to manifestation of coexisting autoimmunologic diseases. Treatment is difficult, long-lasting and sometimes it does not show expected results. There are four groups of medicine to administer. They stimulate hair-regrowth, but do not prevent hair loss.